Pengembangan E-LKPD Liveworksheet melalui Model Project Based Learning Materi Ekosistem Meningkatkan Berpikir Kritis dan Self-Compassion Siswa SDN 2 Tanjungsari - Julia Masrifatin; Mohamad Fatih; Isna Khuni Mualimah (Science and Education Journal (SICEDU), 2026)
This study aimed to develop a Liveworksheet-assisted Electronic Student Worksheet (E-LKPD) through the Project Based Learning (PjBL) model on the harmonious ecosystem topic to improve fifth-grade elementary students’ critical thinking skills and self-compassion. The study employed a Research and Development (R&D) method using a modified Borg and Gall model consisting of seven stages: identifying potential and problems, data collection, product design, design validation, design revision, product testing, and final revision. The participants were 21 fifth-grade students of SDN 2 Tanjungsari, Blitar City. Data were collected through observations, interviews, questionnaires, and tests. The data were analyzed using quantitative descriptive techniques, paired sample t-test, and MANOVA. The results showed that the developed E-LKPD achieved validation scores of 92% from material experts, 90% from media experts, and 88% from language experts, indicating a highly valid category. Teacher and student responses also showed that the product was highly feasible and attractive for classroom implementation. The results of the paired sample t-test revealed significant improvements in students’ critical thinking skills and self-compassion after using the E-LKPD. Furthermore, the MANOVA results indicated a significant simultaneous effect on both variables. Therefore, the developed E-LKPD was considered valid, feasible, and effective for science learning in elementary schools.